Aggression in martial arts coaches and sports performance with the COVID-19 pandemic in the background - a dual processing analysis - Predoiu, R.; Makarowski, R.; Görner, K.; Predoiu, A.; Boe, O.; Ciolacu, M.; Grigoroiu, C.; Piotrowski, A. (Archives of Budo, 2022)
Background and Study Aims: Considering the dual processing model, human behaviour is guided by implicit and explicit processing. Implicit or automatic processing is essentially a spontaneous processing that occurs in the absence of conscious control. Coaches` aggression can be, therefore, assessed both explicitly and implicitly. The aims of our research were to identify what is specific for successful martial arts coaches, considering aggression and whether implicit aggression is a better predictor of sports performance than explicit aggression. Material and Methods: Sixty-two martial arts coaches took part in the study. For assessing explicit aggression, Buss-Perry Aggression Questionnaire and the Romanian adaptation of the Makarowski`s Aggression Questionnaire were used. Implicit aggression was measured through a test derived from the Implicit Associations Test (IAT) for self-concept measurement, using the 20+40 trials subdivision and the classic 7-block version. Results: Coaches with international and national performances associated aggression (measured IAT) with others at a stronger level (M = 0.46 ±0.010), compared to novice coaches, at the beginning of their career (M = 0.38 ±0.08). The average value for verbal aggression is significantly higher [t(60) = 2.12, p = 0.038] in successful coaches (which obtained a slightly above average score) compared to beginners/ young coaches (below average score). The effect size index (Hedge`s g = 0.51) shows a moderate difference between the results (for verbal aggression) of successful coaches and coaches at the beginning of their career. The binomial logistic regressions are statistically significant (p<0.05; "Omnibus test - Model"). The logistic regression models were statistically significant: VA - ?2(1) = 4.48, p<0.05; IAT - ?2(1) = 10.29, p<0.005. In the case of martial arts coaches, implicit aggression test is a better predictor of sports performance than explicit (verbal) aggression.